Bibliometric analysis of knowledge maps and future trends of TIM-3 in cancer - Lv, Shuchi; Huang, Shanchuan; Li, Langming; Lin, Kaifeng; Zhang, Hongliang; Huang, Yuqi (Frontiers in Oncology, 2026)
ObjectivesThis study conducted a bibliometric analysis of TIM-3 research in cancer in the past 25 years and expounded on the mainstream countries, institutions, authors, journals, and publications in this field. It intuitively depicts the evolution trajectory and future direction of TIM-3 research in the past 25 years.Materials and methodsThe published literature on the role of TIM-3 in cancer research was retrieved from the WoSCC and PubMed databases. Various bibliometric tools (including VOSviewer and CiteSpace) were used to identify the historical features, the evolution of active topics, and emerging trends.ResultsA total of 1466 articles were retrieved, with the main contributors including China, the United States, and Japan. The journal with the most published articles was Frontiers in Immunology. Anderson AC is the core author of this research field. The most common keyword is “TIM-3.” Furthermore, 37 clinical trial articles in the PubMed database were included. The analysis indicated that the main contributing countries were the United States, China, and Japan, with the United States being the pioneer of TIM-3 clinical research in cancer. Among these authors, Leena Gandhi published the highest number of articles. Keyword analysis indicated that most researchers experimentally validated and analyzed the characteristics of immune cells and biomarkers within the tumor microenvironment to predict clinical responses and mechanisms of resistance in cancer immunotherapy.ConclusionThe findings of this bibliometric study help researchers discover important topics and future research objectives by offering insights into the existing state and trends of TIM-3 in cancer.